2013
DOI: 10.1002/prot.24323
|View full text |Cite
|
Sign up to set email alerts
|

Alternative zinc‐binding sites explain the redox sensitivity of zinc‐containing anti‐sigma factors

Abstract: Certain bacterial zinc-containing anti-sigma (ZAS) factors respond sensitively to thiol-induced oxidative stress by undergoing conformational changes, which in turn reduce binding affinities for their cognate sigma factors. This redox sensitivity provides a mechanism for coping with oxidative stress by activating the transcription of antioxidant genes. Not all ZAS proteins are redox-sensitive, but the mechanism of redox sensitivity is not fully understood. Here we propose that alternative zinc-binding sites de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Heo et al . 31 have suggested that the differences in redox sensitivity of different ZAS proteins are due to the differences in electronegative residues and binding of alternative zinc ions. However, as our data above illustrate, additional zinc ions play little or no role in the redox-sensing ability of RsrA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heo et al . 31 have suggested that the differences in redox sensitivity of different ZAS proteins are due to the differences in electronegative residues and binding of alternative zinc ions. However, as our data above illustrate, additional zinc ions play little or no role in the redox-sensing ability of RsrA.…”
Section: Resultsmentioning
confidence: 99%
“… 26 have suggested that zinc has little role to play in σ R binding and redox sensing, respectively, while Heo et al . 31 suggest that multiple zinc ions bind to RsrA to modulate its redox reactivity 31 . We re-assessed the stoichiometry of zinc binding before dissecting the redox-sensing mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…Among these residues, those that flank the two cysteines of the HCC motif (E39, E40, L45 and E46) contribute significantly to redox sensitivity (Jung et al , ). Protein modeling and zinc docking studies on redox‐sensitive vs. ‐insensitive ZAS factors suggests that a zinc ion can probabilistically occupy one of multiple sites in redox‐sensitive ZAS, thereby increasing the susceptibility of zinc‐coordinating cysteine residues to oxidation (Heo et al , ). This implies that the flexibility in zinc binding could contribute to redox‐sensitivity.…”
Section: Determinants Of Rsra Redox Sensitivitymentioning
confidence: 99%
“…The well-studied mechanism of redox-induced conformational change involves metal-derived redox reactions that occur frequently with changes in cellular thiol balance ( Ilbert et al, 2006 ; Fan et al, 2009 ). Conformational changes resulting from Zn release in proteins such as Hsp33 ( Ilbert et al, 2006 ), metallothionein ( Oteiza, 2012 ), thioredoxin 2 from Escherichia coli ( El Hajjaji et al, 2009 ), PKC ( Zhao et al, 2011 ), and antisigma factor RsrA ( Heo et al, 2013 ) routinely occur following oxidative stress. The coordinating cysteine residues in the zinc finger cluster form intramolecular disulfides releasing Zn which leads to unfolding of the redox-responsive region in Hsp33.…”
Section: Does Oxidation Modulate Protein Conformation?mentioning
confidence: 99%